Double whammy: the genetic variants in CECR2 and high Hcy on the development of neural tube defects - Bai, Baoling; Jiang, Qian; Liu, Lingyun; Liu, Changyun; Zhang, Qin (Frontiers in Genetics, 2023)
Neural tube defects (NTDs) are serious congenital malformations. The etiology of NTDs involves both genetic and environmental factors. Loss of Cecr2 in mice has been shown to result in NTDs. Our previous study indicated that high homocysteine (HHcy) levels could further reduced the expression level of Cecr2. The aim of this study was to evaluate the genetic contribution of the chromatin remodeling gene CECR2 in human and to examine whether HHcy can synergistically affect the expression of the protein. We carried out next-generation sequencing (NGS) of NTDs target genes in 373 cases of NTDs and 222 healthy controls, and discovered nine NTD-specific rare mutations in CECR2. We then used functional assays to select and evaluate four missense variants: p.E327V, p.T521S, p.G701R and p.G868R. Western blotting demonstrated significantly reductions in Cecr2 protein expression in the E9.5 mouse ectodermal stem cell line NE-4C transfected with plasmids expressing p.E327V, p.T521S, p.G868R or a recombinant simultaneously containing all four mutations (named as 4Mut). Superimposition of treatment with hcy thiolactone (HTL), a highly reactive homocysteine metabolite, enhanced the reduced expression of Cecr2, accompanied with significantly increased activities of the apoptotic molecule Caspase3, which might induce NTDs. Folic acid (FA) supplementation effectively restored the decline in Cecr2 expression caused by CECR2 mutation and HTL treatment, and subsequently reduced apoptosis. Our findings demonstrate a synergistic effect between HHcy and CECR2 genetic variation in NTDs, and highlight the phenomenon of gene–environment interactions in NTDs.